Success of modified Fujita technique uvulopalatoplasty with septoplasty in the management of obstructive sleep apnea syndrome - Akın, Okan; Fidan, Vural; Samim, Erdal (ENT Updates, 2012)
Objective: The aim of this study was to investigate the clinical efficacy of modified Fujita technique uvulopalatoplasty (UPPP) with nasal surgery in patients with simple snoring and obstructive sleep apnea syndrome (OSAS). Methods: A total of 12 consecutive OSAS patients (mean age 46.08±7.16 years) who underwent modified Fujita technique UPPP with nasal surgery were included in the study. Pre and postoperative subjective symptoms and polysomnographic data were compared. Results: Following simultaneous nasal-oropharyngeal surgery, the AHI significantly decreased (from 41.8±22.5 to 19.3±12.6 events per hour; p0.05). Conclusion: Single-staged modified UPPP with nasal surgery is an available and relatively safe surgical approach in OSAS patients with nasal obstruction.